Cardiac Injury and Clinical Course of Patients With Coronavirus Disease 2019 - Wang, Yushi; Zheng, Yang; Tong, Qian; Wang, Lihui; Lv, Guorui; Xi, Ziwei; Liu, Wei (Frontiers in Cardiovascular Medicine, 2020)
Background: Cardiac injury is recognized as one of the most common critical complications during exacerbation of coronavirus disease 2019 (COVID-19). This study aimed to investigate the effect of cardiac injury on the clinical course of COVID-19 and to examine its potential mechanism and treatments. Methods and Results: A total of 222 hospitalized patients with COVID-19 from Wuhan were selected for the study during February 10 to March 28, 2020. Demographic, laboratory, and clinical data on admission and during hospitalization were compared between patients with COVID-19 with or without cardiac injury. On admission, cardiac injury (n = 29) was associated with advanced age, more underlying coronary artery disease, and a lower Pao2. Troponin levels were correlated with inflammatory markers (C-reactive protein: r = 0.348, P < 0.001; interleukin 6: r = 0.558, P < 0.001) and d-dimer levels (r = 0.598, P < 0.001). During hospitalization, another six patients suffered from cardiac injury and cardiac injury (n = 35), resulting in higher rates of ventilation (invasive: 51.4 vs. 1.6%, P < 0.001; non-invasive: 31.4 vs. 1.1%, P < 0.001) and mortality (54.3 vs. 1.1%, P < 0.001). Cardiac injury on admission was a predictive factor for mortality (adjusted hazard ratio = 4.73, 95% confidence interval = 1.35–16.63, P = 0.015). Receiver operating characteristic curve analysis showed that, on admission, a troponin level of 36.35 pg/mL was predictive for mortality with a sensitivity of 73.7% and a specificity of 92.1%. Conclusions: Cardiac injury complicates the disease course and increases the mortality rate of COVID-19. Troponin levels should be checked at admission and during hospitalization for triage, better monitoring, and managing those with COVID-19, especially in the most severe patients. Condensed Abstract: Cardiac injury is not uncommon in COVID-19. In a cohort of 222 patients with COVID-19, cardiac injury was found in 29 patients on admission and in another 6 patients during hospitalization. The admission level of troponin was well-correlated with inflammatory factors and d-dimer levels and strongly predicted mortality. Cardiac injury is a manifestation secondary to hypoxia and systemic infection, but which nevertheless further complicates the disease course and increases the mortality rate. Troponin levels should be checked at admission and during hospitalization for triage, better monitoring, and managing those with COVID-19, especially in the most severe patients.